Effect in positioning gold nanoparticle inside plasmonic solar cell on absorption, reflection and transmission - M. Nasar, Norasikin; Abdul-Kahar, Rosmila; Amir Hamzah, Nor Shamsidah; Esa, Fahmiruddin; Rodhuan, Mirza Basyir (HRPub, 2019)
Gold nanoparticle has been explored in different ways to enhance the absorption of light and improve the efficiency of plasmonic solar cell. In this study, various positions of a gold nanoparticle which are at 115 nm, 230 nm and 305 nm measured vertically from the bottom of the solar cell to the centre of gold nanoparticle embedded into silicon layer of plasmonic solar cell is demonstrated using numerical simulation. The aim is to investigate the absorption, reflection and transmission percentage with different wavelength in different position of gold nanoparticle in plasmonic solar cell. The numerical results showed that the highest absorption and lowest reflection and transmission occurred at position 305 nm in the range 100 nm to 1000 nm compared to the simulation without nanoparticle and other position. The overall simulation results proved that at position 305 nm of gold nanoparticle which is near to the top layer is more efficient because this position has high electric field intensity in visible range.